2023
DOI: 10.1130/g50810.1
|View full text |Cite
|
Sign up to set email alerts
|

Melting of fault gouge at shallow depth during the 2008 MW 7.9 Wenchuan earthquake, China

Abstract: Typical rocks at shallow depths of seismogenic faults are fluid-rich gouges. During earthquakes, on-fault frictional heating may trigger thermal pressurization and dynamic fault weakening. We show that frictional melting, rather than thermal pressurization, occurred at shallow depths during the 2008 MW 7.9 Wenchuan earthquake, China. One year after the Wenchuan earthquake, we found an ~2-mm-thick, glass-bearing pseudotachylyte (solidified frictional melt) in the fault gouges retrieved at 732.6 m depth from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, the significant fine‐size of angular quartz grains within the fault gouge, truncated calcite veins (Figure 6e), injection gouge veins containing angular particles (Figures 6e, 7b, and 7e), as well as the consistent position between the black fault gouge and fault trace, all suggest that the 3 to 5 cm‐thick black gouge is formed by seismic (or stick‐slip) fault behavior, and that it represents the principal slip zone (PSZ) of the Qianning segment of the Xianshuihe fault. Although the exact thickness of the PSZ associated with a single paleoseismic event is impossible to determine, the rapid implementation of scientific drillings in seismic fault zones after a large earthquake might provide some essential data: for example, the 50–300 μm or 1‐2 mm‐thick fault gouges formed by the 1999 Chi‐Chi earthquake ( M w 7.6) in Taiwan (e.g., Heermance et al., 2003; Kuo et al., 2011), and the ∼200 μm‐thick ultrafine‐grained slip zone and ∼2 mm‐thick glass‐bearing pseudotachylyte which were formed by the 2008 Wenchuan earthquake ( M w 7.9) in the Longmenshan's Yingxiu‐Beichuan fault zone (Kuo et al., 2014; H. Wang et al., 2023). Considering the reworked gouge clasts in BG 2 (Figures 7c and 7d) and the injection gouge vein wedging into BG 1 from BG 3 (Figure 7e), the 3 to 5 cm‐thick PSZ gouge in the Cunielongba exposure thus records repeated seismic events.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the significant fine‐size of angular quartz grains within the fault gouge, truncated calcite veins (Figure 6e), injection gouge veins containing angular particles (Figures 6e, 7b, and 7e), as well as the consistent position between the black fault gouge and fault trace, all suggest that the 3 to 5 cm‐thick black gouge is formed by seismic (or stick‐slip) fault behavior, and that it represents the principal slip zone (PSZ) of the Qianning segment of the Xianshuihe fault. Although the exact thickness of the PSZ associated with a single paleoseismic event is impossible to determine, the rapid implementation of scientific drillings in seismic fault zones after a large earthquake might provide some essential data: for example, the 50–300 μm or 1‐2 mm‐thick fault gouges formed by the 1999 Chi‐Chi earthquake ( M w 7.6) in Taiwan (e.g., Heermance et al., 2003; Kuo et al., 2011), and the ∼200 μm‐thick ultrafine‐grained slip zone and ∼2 mm‐thick glass‐bearing pseudotachylyte which were formed by the 2008 Wenchuan earthquake ( M w 7.9) in the Longmenshan's Yingxiu‐Beichuan fault zone (Kuo et al., 2014; H. Wang et al., 2023). Considering the reworked gouge clasts in BG 2 (Figures 7c and 7d) and the injection gouge vein wedging into BG 1 from BG 3 (Figure 7e), the 3 to 5 cm‐thick PSZ gouge in the Cunielongba exposure thus records repeated seismic events.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the presence of multiple generations of pseudotachylyte outcropped along the Yingxiu-Beichuan fault zone, H. Wang et al (2015) suggested that friction melt lubrication, thermal pressurization, and mechanical lubrication could operate together during the coseismic slip. Recently, however, with finding of melted fault gouge (present as glass-bearing pseudotachylytes) at shallow depth of the rupture zone, frictional melting, rather than thermal pressurization, is suggested to have occurred at shallow depths during the Wenchuan earthquake (H. Wang et al, 2023). Obviously, these make the dynamic weakening of the faults, especially the occurrence of thermal pressurization, still debated.…”
Section: Implications For Fault Slip Weakeningmentioning
confidence: 99%
“…0.01-0.3) over a given slip weakening distance Dw (Di . They include flash heating and associated weakening at early stages of slip (Proctor et al, 2014;Yao et al, 2016a, b), frictional melting at grain contacts (Wang et al, 2023), thermal decomposition (De Paola et al, 2011), bulk thermo-mechanical pore fluid pressurization (TP mentioned above; Aretusini et al, 2021;Faulkner et al, 2011;Hunfeld et al, 2021;Togo et al, 2011), silica gel production and lubrication (Di Toro et al, 2004;Rowe et al, 2019), thermochemical pressurization (Brantut et al, 2010), thermally activated super-plasticity (Chen et al, 2021;De Paola et al, 2015), pore water phase transitions from the liquid to the gaseous or supercritical state (Chen et al, 2017;Ferri et al, 2010: Oohashi at al., 2011, and flash pressurization (combined flash heating and TP at asperity contacts; Chen et al, 2023;Yao et al, 2018). The activation of any of the above-mentioned weakening mechanisms is typically dependent on the amount of frictional heat generated, which is controlled by experimental conditions (e.g.…”
Section: Strain Localization Frictional Heating and Dynamic Weakening...mentioning
confidence: 99%
“…Feng et al, 2023;Gomila et al, 2021;Violay et al, 2013Violay et al, , 2014Violay et al, , 2015Violay et al, , 2019Yao et al, 2023) or shearing of mm-thick simulated fault gouge layers (e.g. Boulton et al, 2017;Chen et al, 2023;Hunfeld et al, 2021;Kuo et al, 2021Kuo et al, , 2022Wang et al, 2023;Yao et al, 2018). Across different lithologies, these studies have consistently reported the effectiveness of TP at scales ranging from the bulk shear zone to grain-to-grain asperity contacts.…”
Section: Introductionmentioning
confidence: 99%